2006
DOI: 10.1038/msb4100094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HER2 overexpression on cell signaling networks governing proliferation and migration

Abstract: Although human epidermal growth factor receptor 2 (HER2) overexpression is implicated in tumor progression for a variety of cancer types, how it dysregulates signaling networks governing cell behavioral functions is poorly understood. To address this problem, we use quantitative mass spectrometry to analyze dynamic effects of HER2 overexpression on phosphotyrosine signaling in human mammary epithelial cells stimulated by epidermal growth factor (EGF) or heregulin (HRG). Data generated from this analysis reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
254
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(271 citation statements)
references
References 59 publications
10
254
0
Order By: Relevance
“…No phosphorylation events were identified in this region of the protein (232-245) in either spot 26 or 27; however, this peptide sequence was not detected in the analysis of spot 29. Phosphory-lation of Y236 has been previously associated with migration [24]. The exact site of the phosphorylation was not established during our analysis.…”
Section: Discussionmentioning
confidence: 82%
“…No phosphorylation events were identified in this region of the protein (232-245) in either spot 26 or 27; however, this peptide sequence was not detected in the analysis of spot 29. Phosphory-lation of Y236 has been previously associated with migration [24]. The exact site of the phosphorylation was not established during our analysis.…”
Section: Discussionmentioning
confidence: 82%
“…Our survival analysis showed that ERBB2-amplifying expansive carcinomas have worse prognosis than those with the same growth pattern lacking that genetic alteration (P ¼ 0.011), which we did not observe in infiltrating gastric carcinomas (P ¼ 0.863). Recent data published by Wolf-Yadlin et al (2006) might explain the different effect of ERBB2 amplification in carcinomas with different growth patterns. These authors suggested that ERBB2 overexpression promotes increased cell migration but has minimal effect on cell proliferation in cells stimulated by epidermal growth factor or heregulin (Wolf-Yadlin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data published by Wolf-Yadlin et al (2006) might explain the different effect of ERBB2 amplification in carcinomas with different growth patterns. These authors suggested that ERBB2 overexpression promotes increased cell migration but has minimal effect on cell proliferation in cells stimulated by epidermal growth factor or heregulin (Wolf-Yadlin et al, 2006). Thus, ERBB2 amplification could increase cell migration in expansive carcinomas, whereas infiltrative carcinomas, which already have a strong invasive potential, do not acquire additional advantage from ERBB2 amplification.…”
Section: Discussionmentioning
confidence: 99%
“…2 HER2 overexpression, a molecular oncodriver in several tumor types including 20-25% of BCs, 3 is associated with an aggressive clinical course, resistance to chemotherapy, and a poor overall prognosis. 4,5 In incipient BC, HER2 overexpression is associated with enhanced invasiveness, 6 tumor cell migration, 7 and the expression of proangiogenic factors, 8 suggesting a critical role for HER2 in promoting a tumorigenic environment. Although HER2-targeted therapies (i.e., trastuzumab), in combination with chemotherapy, have significantly improved survival in HER2 pos BC, 9 a substantial proportion of patients become resistant to such therapies.…”
Section: Introductionmentioning
confidence: 99%